Crowdfunding as an alternative financing solution for SMEs in Algeria - Khodheir Latifa Salima; Ouguenoune Hind (Dirassat Journal Economic Issue, 2021)
The purpose of this study is to present crowdfunding as a new financing alternative for SMEs, which, despite their small size, represent a major challenge for economic growth in Algeria. Therefore, by offering several advantages compared to traditional bank financing, crowdfunding further encourages project leaders to implement their innovative ideas. The crowdfunding present in the world has contributed to the financing of a significant number of emerging companies in the field of entrepreneurship. Despite the rapid evolution of this new mode of financing, the crowdfunding is experiencing slow growth in the Maghreb countries in general and Algeria in particular. This delay is due to the lack of awareness and initiatives on the part of the authorities. Despite the effort made by the Algerian authorities through the complementary finance law of 2020 to regularize this mode of financing, Algeria will have to make even greater efforts to raise awareness of the use of this mode of financing.